PEMBAGIAN HARTA WARISAN TERHADAP ANAK ANGKAT (KOPAK) PADA MASYARAKAT ADAT DAYAK KANAYATN DESA SIDAS KECAMATAN SENGAH TEMILA KABUPATEN LANDAK - NIM. A1011211267, VICTORY MEIDYLA MAMURAJA (Fakultas Hukum Universitas Tanjungpura, 2025)
AbstractThe Dayak Kanayatn indigenous community in Sidas Village, Sengah Temila District, Landak Regency is an indigenous community that adheres to an individual inheritance system, which means that the inheritance given by the heir to his heirs can be owned individually and the heirs have the right to manage and use it. In the Dayak Kanayatn indigenous community, every child has the same position to become an heir, as well as adopted children. Adopted children in the Dayak Kanayatn indigenous community are called